Companion to psychiatric studies - Johnstone, Eve C.; Owens, David Cunningham; Lawrie, Stephen M.; McIntosh, Andrew M.; Sharpe, Michael D. (Churchill Livingstone/Elsevier, 2010)
Covering the subject of psychiatric studies [both basic sciences and clinical practice], this book is suitable for psychiatry trainees, especially candidates for postgraduate psychiatry exams, and qualified psychiatrists.